Fidelio at the Salzburg Festival, 1938 - Wiener Philharmoniker:::Creator:::::::::::: (Kiesel; Argentina; Salzburg, 2020)
Program for a performance of Fidelio directed by Hans Knappertsbusch at the Salzburg Festival in 1938. Includes synopsis in German, English, and French.